(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
Materials and methods: herbarium collections, literature data, field observations. Nomenclature: POWO 2024. Results: In the flora of Ukraine, the Malvales order includes three families – Cistaceae, Malvaceae (incl. Tiliaceae) and Thyme-laeaceae. The Cistaceae family includes three genera: Cistus (C. tau-ricus), Fumana (incl. Fumanopsis) – 3 species, and Helianthemum – 12 species, of which two Crimean ones (H. lasiocarpum, H. ledi-folium) require new confirmation. Significant nomenclatural changes occurred in the genus Helianthemum. The Malvaceae family, including the Tiliaceae family, in the flora of Ukraine is represented by 16 genera (Abelmoschus, Abutilon, Alcea, Althaea, Anoda, Callianthe, Corynabution, Gossypium, Hibiscus, Kitaibelia, Malope, Malva (incl. Lavatera), Malvella, Ripariosida, Sida, Tilia) and 49 species (together with subspecies, wild and cultivated plants). The genus Lavatera is included in the genus Malva, since the main morphological feature that previously distinguished the genera (the leaves of the subcalyx attached to the base in Lavatera and free in Malva) was not sufficient to distinguish them. In the flora of Ukraine, the genus Malva is represented by 9 species. Malva alcea is a new species for Ukraine, which was previously not listed in national records. The species Sida hermaphrodita, which is sometimes cultivated in Ukraine as a technical (fibrous) and fodder plant and is brought to the fields as a weed, is now separated from the genus Sida into a separate monotypic genus Ripariosida (R. hermaphrodita). Nomenclatural and taxonomic changes occurred in the genus Tilia. The family Thymelaeaceae in Ukraine is represented by two genera (Daphne, Thymelaea) and 6 species.